Predictors of Perinatal Mortality Associated With Placental Abruption: A Single Center Experience With 200 subjects - Gülseren Yılmaz; Aysu Akça; Hüseyin Kıyak; Ziya Salihoğlu (Erciyes Medical Journal, 2019)
Objective: Despite recent advances in prenatal diagnostic techniques, placental abruption (PA) remains one of the most significant causes of maternal morbidity and perinatal mortality. The purpose of the present study is to summarize the current knowledge concerning PA and to present maternal and fetal outcomes of the patients admitted to our clinic who underwent cesarean delivery for PA. Materials and Methods: All the consecutive patients enrolled in our clinic and diagnosed with PA between January 2015 and December 2018 were enrolled in this retrospective study. Data regarding demographics, operation details, and the postoperative course included blood transfusions, development of maternal and fetal complications, and laboratory measurements were collected from the electronic institutional database. Results: A total of 200 patients were recruited in this retrospective study. No maternal death was observed during the in-hospital course. Uterine rupture developed in 6 (3%) subjects, severe hemorrhage occurred in 28 subjects (14%), and fetal and neonatal mortality was observed in 10 (5%) subjects. Logistic regression analyses indicated that fibrinogen levels prior to delivery (p=0.039), gestational age (p=0.005), smoking (p=0.044), and maternal systolic blood pressure (p=0.013) were independent predictors for fetal and neonatal mortality. Conclusion: The maternal and perinatal mortality observed in our study population is favorable as compared to previous results. Fibrinogen levels prior to delivery, gestational age, smoking, and maternal systolic blood pressure were independently predictive for fetal and neonatal mortality in subjects with PA.